2004
DOI: 10.1143/jjap.43.1729
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasma Nitridation Impact on Lateral Extension Profile in 50 nm N-MOSFET by Scanning Tunneling Microscopy

Abstract: The electrical performances of sub-50-nm n-metal-oxide-semiconductor field effect transistors (n-MOSFETs) are improved when a plasma nitridation process is used after the gate electrodes are formed. The maximum drive current is increased by 2% and the minimum gate length is shrunk by 5% while the off-leakage current is maintained. Inverse modeling suggested that these improvements were due to nitridation-induced changes in the two-dimensional carrier profile, and scanning tunneling microscopy confirmed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Again, the apparent height diŠerence of ¿0.3 nm emerges not from the physical height diŠerence but from the potential variation between the regions with diŠerent dopant concentrations. Several groups have employed such electroni-cally induced morphology for assessment of the device implantation strategy, 44,45) and delineation of p-n junctions. 30,47,50) 3.2 Dopant atom counting The direct STM-based dopant proˆling method is to count the number of dopant atoms appearing near the surface atomic plane.…”
Section: Constant Current Stm Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the apparent height diŠerence of ¿0.3 nm emerges not from the physical height diŠerence but from the potential variation between the regions with diŠerent dopant concentrations. Several groups have employed such electroni-cally induced morphology for assessment of the device implantation strategy, 44,45) and delineation of p-n junctions. 30,47,50) 3.2 Dopant atom counting The direct STM-based dopant proˆling method is to count the number of dopant atoms appearing near the surface atomic plane.…”
Section: Constant Current Stm Imagingmentioning
confidence: 99%
“…In particular, current imaging tunneling spectroscopy (CITS) was found to be highly eŠective in revealing the electronic structure of p-n junctions and MOSFET devices. 18,28,30,[44][45][46][47][48][49] In this technique, the tip-sample gap is determined by the demanded tunneling current at a given bias voltage. During scanning in the constant current mode, a current-voltage (I t -V s ) spectrum is measured at each point on the sample area while holding tipsample gap.…”
Section: Current-voltage Spectroscopy and Onset Voltagesmentioning
confidence: 99%
“…[3] Current response dI was measured with a lock-in amplifier at each point in the topographical image, and the LWF value was calculated from measured (dI/dZ) signal as [ Carrier density mapping Samples of n-MOSFET devices were prepared with gate lengths in the range of 12 -150 nm according to the normal fabrication process described in Ref. [1]. Cross sections of the devices were prepared by ultra-fine polishing to expose (110) surfaces.…”
Section: Vgm Spectroscopy Techniquementioning
confidence: 99%
“…Scanning tunneling microscopy (STM) is a promising technique as it has shown the ability to visualize individual impurity atoms and to determine variation of the surface potential on passivated Si surfaces and device cross-sections. [1,2] We have already shown that spatial variation of the surface potential due to negative acceptor charges beneath the Si surface were obtained in local work function (LWF) maps on oxygen-passivated surfaces of Si(111) and (110) by vacuum-gap modulation (VGM) STM spectroscopy. [3] In this paper we investigate origin of the LWF variation on cross sections of small n-MOSFET devices with gate lengths in a range of 12 -150 nm by the VGM-STM spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Kelvin-probe force microscopy ͑KFM͒, 3-5 scanning capacitance microscopy ͑SCM͒, 6-19 scanning capacitance force microscopy ͑SCFM͒, 20-22 scanning spreading resistance microscopy ͑SSRM͒, 23-28 nano-scale potentiometry, 29,30 and scanning tunneling microscopy [31][32][33][34] ͑STM͒ have been used to investigate cross-sectioned semiconductor devices. Among them, Kelvin-probe force microscopy ͑KFM͒, 3-5 scanning capacitance microscopy ͑SCM͒, 6-19 scanning capacitance force microscopy ͑SCFM͒, 20-22 scanning spreading resistance microscopy ͑SSRM͒, 23-28 nano-scale potentiometry, 29,30 and scanning tunneling microscopy [31][32][33][34] ͑STM͒ have been used to investigate cross-sectioned semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%